33. A CASE REPORT: A SUCCESSFUL APPLICATION OF THE NEW “A NOVEL FIVE-STEP REDUCTION TECHNIQUE ARYTENOID DISLOCATION” UNDER ENDOSCOPY AT CAN THO UNIVERSITY OF MEDICINE AND PHARMACY HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2024)
The arytenoid disarticulation is a rare clinical condition, often occurring as a secondary complication after endotracheal intubation, during anesthesia, or sometimes due to external trauma to the larynx. At the Ear-Nose-Throat (ENT) department of Can Tho University of Medicine and Pharmacy hospital, we have one patient with arytenoid disarticulation caused by a rope cutting into the neck.Case Report: The patient presented with hoarseness and left arytenoid cartilage repositioning under endoscopic laryngeal surgery. The patient was diagnosed with arytenoid disarticulation following an accident 2 weeks prior, where a rope cut into the neck while the patient was riding a motorcycle at approximately 30-40 km/h. After surgery, the patient's voice almost returned to normal, and the arytenoid cartilage was restored to its anatomical position. Currently, there is no consensus on the devices and methods for reducing arytenoid disarticulation. Some international studies have reported successful treatment of arytenoid disarticulation using the "5-step reduction technique for arytenoid dislocation" under laryngeal endoscopy.Conclusion: To implement a new method for treating arytenoid disarticulation, we report a successful case of treating arytenoid disarticulation using the "5-step reduction technique for arytenoid dislocation " in a patient following a traffic accident.
Keywords: Arytenoid dislocation; A Novel Five-Step Reduction Technique; Laryngeal injury; Hoarseness